The effect of source animal age, decellularization protocol, and sterilization method on bovine acellular dermal matrix as a scaffold for wound healing and skin regeneration. Issue 2 (6th October 2022) - Mansour, Reyhaneh Nassiri; Karimizade, Ayoob; Enderami, Seyed Ehsan; Abasi, Mozhgan; Talebpour Amiri, Fereshteh; Jafarirad, Abdolreza; Mellati, Amir
Abstract: Background: Healing the full‐thickness skin wounds has remained a challenge. One of the most frequently used grafts for skin regeneration is xenogeneic acellular dermal matrices (ADMs), including bovine ADMs. This study investigated the effect of the source animal age, enzymatic versus non‐enzymatic decellularization protocols, and gamma irradiation versus ethylene oxide (EO) sterilization on the scaffold. Methods: ADMs were prepared using the dermises of fetal bovine or calf skins. All groups were decellularized through chemical and mechanical methods, unless T‐FADM samples, in which an enzymatic step was added to the decellularization protocol. All groups were sterilized with ethylene oxide (EO), except G‐FADM which was sterilized using gamma irradiation. The scaffolds were characterized through scanning electron microscopy, differential scanning calorimetry, tensile test, MTT assay, DNA quantification, and real‐time PCR. The performance of the ADMs in wound treatment was also evaluated macroscopically and histologically. Results: All ADMs were effectively decellularized. In comparison to FADM (EO‐sterilized fetal ADM), morphological, and mechanical properties of G‐FADM, T‐FADM, and CADM (EOsterilized calf ADM) were changed to different extents. In addition, the CADM and G‐FADM were thermally more stable than the FADM and T‐FADM. Although all ADMs were noncytotoxic, the wounds of the FADM, T‐FADM, and G‐FADM groups were contracted to almost 30.0% of the original area on day 7, significantly faster than the CADM (17.5% ± 1.7) and control (12.2% ± 1.59) groups. However, by day 21, all ADMs were mostly closed except for the untreated group (60.1 ± 1.8). Conclusion: Altogether, fetal source and EO‐sterilized samples performed better than calf source and gamma‐sterilized samples unless in some mechanical properties. There was no added value in using enzymatic treatment during the decellularization process. Our results suggest that the age, decellularization, and sterilization methods of animal source should be selected based on the clinical requirements. Abstract : Summary of the ADM's preparation using different sources of animal age, decellularization protocols, and sterilization methods.